Tree Planting Constraints in Traditional Agroforestry Practices in Dry Lands of Sub Montane North Western Himalayas - Sehgal, Sandeep; Abidi, Raza Ali (Indian Forester, 2015)
The specific objective of the study was to describe the socio-economic characteristics of the stakeholders in sub montane North Western Himalayan dry lands, identify the different agroforestry practices prevalent in the area, the types of trees commonly planted by the farmers along with their uses, perception of farmers about agroforestry and the constraints faced by the farmers in planting trees. A sample of 180 randomly selected respondents from 4 blocks of district Samba viz., Vijaypur, Samba, Gaghwal and Parmandal were interviewed through a pre-structured interview schedule in person and the data so collected were analyzed using statistical software to draw conclusions. The average household size consisted of 7 people with an average age of 53 years. Boundary plantation (39.4%) was the major agroforestry practice, followed by scattered planting (35.0%), block planting (15.6%) and intercropping (10%). Tree components in the area included horticulture and forest tree species. The socio economic and ecological benefits derived by farmers from the planted trees and the major constraints faced by farmers have been drawn.